Perbandingan Algoritma Time Series Dan Fuzzy Inference System Dalam Analisis Data Deret Waktu - Fungki Wahyu; Billy Hendrik (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Time series data analysis is a crucial process for understanding patterns and trends within temporal data. In this endeavor, two primary approaches have emerged: Time Series algorithms, which focus on statistical modeling, and the Fuzzy Inference System (FIS), which adopts fuzzy logic. This article delineates a comparison between these two approaches within the context of time series data analysis.Firstly, Time Series algorithms, such as ARIMA and ETS, offer a robust approach to modeling statistical patterns within temporal data. By considering autoregressive (AR) and moving average (MA) components, along with differencing effects within the time series, these algorithms can identify trends, seasonality, and other fluctuations. However, these algorithms tend to be more complex and rely on a profound understanding of statistics.Secondly, the Fuzzy Inference System (FIS) employs fuzzy logic principles to address uncertainty in time series analysis. Utilizing fuzzy membership functions and rule-based logic, FIS can extract information from data imbued with uncertainty, making it more suitable for situations where data is not entirely clear or structured. Nevertheless, FIS requires expert knowledge to determine appropriate fuzzy rules.The comparison between these two approaches considers several factors, including analysis complexity, data type, and dependence on expert knowledge. Time Series algorithms are better suited for in-depth statistical analysis and mathematical modeling, while FIS is more adept at handling fuzzy data and uncertainty. In some cases, combining both approaches could yield superior results, with FIS assisting in mitigating uncertainty within Time Series models.This article enhances the understanding of these approaches in time series data analysis and provides guidance for practitioners in selecting an approach aligned with their needs. Furthermore, the article underscores the potential for further development in combining the positive aspects of both approaches to tackle more intricate challenges in time series data analysis.